Implementasi Kewenangan Majelis Pengawas Daerah Notaris dalam Pemeriksaan Protokol Notaris di Kota Solok - Putri, Reza; Fendri, Azmi; Syofyan, Syofirman (Universitas Ekasakti, 2023)
Notaries in carrying out their duties for the general public are required to be under the supervision of an institution that is neutral, impartial, and independent. The purpose of this supervision is so that the Notary seriously carries out the duties of his office in accordance with applicable rules and codes of ethics in order to maintain the security of the public who make deeds to the public. Notary Public. Another aim is to avoid Notaries who are irresponsible and do not comply with the Notary's code of ethics. The establishment of a supervisory institution is referred to in Article 1 point 6 of the UUJN which states that the Notary Supervisory Council, hereinafter referred to as the Supervisory Council, is a body that has the authority and obligation to carry out guidance and supervision of Notaries. In Solok City in 2022 there will be eight Notaries, whereas in the examination carried out by the Solok City Regional Supervisory Council in 2022 only four Notaries were examined. Based on this, researchers are interested in conducting further research by analyzing: 1) the implementation of the authority of the Regional Notary Supervisory Council in examining Notary Protocols in Solok City. 2) the obstacles and efforts of the Regional Notary Supervisory Council in carrying out inspections of Notary Protocols in Solok City. This research is descriptive analytical, using an empirical juridical approach. Using primary data as the main material with a study of secondary legal materials. Based on research, it was found that: the implementation of the authority of the Solok City MPD in examining Notary protocols has carried out guidance and supervision related to the implementation which was carried out in 2022, there were around four out of eight Notaries who were not examined. The problem with MPD is that when MPD carries out inspections, several Notaries are not in their offices at the time of the inspection. Which results in Notaries not being checked by the MPD. Efforts made by the MPD were to summon the Notary concerned to appear at the Regional Office of the Ministry of Law and Human Rights to have the protocol checked by the Chair of the MPD and notaries who were not examined were made a priority in the examination for the following year.